Implication of Local Wisdom in Islamic Law Compilation Legislation - Alimuddin, Harwis; Maulidah, Tahani Asri (Universitas Islam Negeri Alauddin Makassar, 2021)
The approach of compromise with local customs (al-‘urf al-khāṣ) in formulation of KHI especially to anticipate the formulation of legal values which is not found in special nas (Koran and Hadits). While the values of the law has grown and evolved as an indigenous norm in the customs of Indonesian society. In addition, the practical level of local customs values that bring goodness and harmony in community life.The possibility of approaching compromise with local customs is not limited to the adoption of local culstoms law values to be adopted and made into Islamic legal provisions, the compromise approach includes also integrating the development of existing Islamic legal values with local customs legal values . The goal is making the provisions of Islamic law more closer to the value of life awareness in society (living law). This kind of methode can be expressed in a phrase: “Islamizing local customs and simultaneously bringing Islamic law into the local customs”.